Solve (z-i)+(z+i)+(z-1)+(z-1)

Since we are dealing with complex numbers and taking its modulus, we can rewrite (z-i)=((-1)(i-z))=(i-z) doing the same for (z-1)=(1-z) we get (i-z)+(z+i)+(1-z)+(z-1)=(i+i+z-z+1+1+z-z) =(2i+2)=4 as we are taking its modulus.

Related Further Mathematics A Level answers

All answers ▸

What are imaginary numbers, and why do we bother thinking about them if they don't exist?


Solve the inequality x^3 + x^2 > 6x


Given that z = a + bj, find Re(z/z*) and Im(z/z*).


A particle is moving in a straight line with simple harmonic motion. The period of the motion is (3pi/5)seconds and the amplitude is 0.4metres. Calculate the maximum speed of the particle.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences